Kyai Hardawalika: Mistisisme Jawa Mataram dan Kemelut Suksesi Takhta Sultan Hamengku Buwana VII (1877-1921) - Hakim, Moh. Taufiqul (Arnawa, 2024)
This research examined the manuscript of Pranatan Yogyakarta Hadiningrat recording the coronation ceremony of Pangeran Juminah as crown prince on 11 November 1895. The event took place during the era of Sultan Hamengku Buwana VII (reigned 1877-1921), which was full of political pressure from the Dutch and political intrigues of court relatives who wanted to take over the Sultan's throne. The manuscript is written in Javanese script. The manuscript in macapat is the collection of a Dutch scholar and missionary Ir. J.L. Moens (1887-1954) which is now stored at the National Library of Indonesia with the number KBG 921. This research highlighted the absence of the Kangjeng Kyai Hardawalika heirloom in the coronation procession. In fact, in the tradition of the Islamic Mataram kingdom, it is a mystical allegory of the power that sustained the reign of the ruling king. Through philological reading, it was found that the absence of Kyai Hardawalika was a mystical-symbolic acknowledgement by a king who obeys and upholds tradition, namely Sultan Hamengku Buwana VII, of the current socio-political conditions. The absence of Kyai Hardawalika showed that the reigning king at that time no longer had the power to support the government. This is because the Sultanate of Yogyakarta was founded on colonial political contracts that were detrimental to the kingdom and the Javanese people in general. === Penelitian ini mengkaji naskah Pranatan Yogyakarta Hadiningrat yang mencatat prosesi upacara penobatan Pangeran Juminah sebagai putra mahkota pada 11 November 1895. Peristiwa tersebut terjadi di era Sultan Hamengku Buwana VII (bertakhta 1877-1921), yang penuh dengan tekanan politik dari Belanda dan intrik politik kerabat istana yang ingin mengambil alih takhta Sultan. Naskah ini ditulis dengan aksara dan berbahasa Jawa. Naskah bermetrum macapat ini merupakan koleksi seorang cendekiawan dan misionaris Belanda Ir. J.L. Moens (1887-1954) yang kini tersimpan di Perpustakaan Nasional RI dengan nomor KBG 921. Penelitian ini menyoroti absesnnya pusaka Kangjeng Kyai Hardawalika dalam prosesi penobatan. Padahal, dalam tradisi kerajaan Mataram Islam, ia merupakan alegori mistis dari kekuatan yang menopang pemerintahan raja yang berkuasa. Melalui pembacan filologis, ditemukan bahwa absennya Kyai Hardawalika merupakan sebuah pengakuan secara mistik-simbolis oleh seorang raja yang taat dan teguh memegang tradisi, yakni Sultan Hamengku Buwana VII terhadap kondisi sosial-politik yang sedang terjadi. Absennya Kyai Hardawalika menunjukkan bahwa raja yang bertakhta saat itu sudah tidak mempunyai kekuatan sebagai penopang jalannya pemerintahan. Pasalnya, Kesultanan Yogyakarta berdiri di atas kontrak-kontrak politik kolonial yang merugikan kerajaan dan orang Jawa pada umumnya.